Handbook of herbs and spices. Volume 3 - Peter, K. V. (Woodhead, 2006)
Annotation This third volume of this comprehensive and authoritative reference continues coverage of key herbs and spices for the food industry. Ensuring the safety of herbs and spices, their use as colourings and flavourings and functional benefits are covered in introductory chapters. Just as in volumes 1 and 2, chapters on individual plants, their production, chemical structure and properties and uses in food processing then follow. CONTENTS Part 1 Improving the safety of herbs and spices: Detecting and controlling mycotoxin contamination; Controlling pesticide and other residues; Irradiation to decontaminate herbs and spices; Other decontamination techniques; Packaging and storage Part 2 Herbs and spices as colourings and flavourings: Pigments from herbs and spices; Volatiles from herbs and spices; Quality testing of spice essential oils and oleoresins. Part 3 Functional benefits of herbs and spices: Herbs, spices and cardiovascular disease; Herbs, spices and cancer; Herb, spices and gut health. Part 4 Individual herbs and spices: Asafoetida; Balm; Caper; Caraway; Cayenne pepper; Chives; Lemongrass; Lovage; Peppermint; Spearmint; Sesame.
Keywords: Herbs.; Spices.; Food industry and trade -- Quality control.; elektronické knihy; electronic books